ANALISIS POSKOLONIAL PADA NOVEL TAK ADA ESOK KARYA MOCHTAR LUBIS - Lupi Saepul Nudin; Sasongko S. Putro; Dedi Yusar (Universitas Pakuan, 2021)
Abstract This research is a postcolonial study describing the resistance that occurred in the novel No Tomorrow by Mochtar Lubis. In this study using descriptive and deconstructive analysis methods. In order to be easy in conducting postcolonial study research, an intrinsic elemental approach is also used. The focus on this study is related to radical and passive resistance and mimicry that occurs in the novel No Tomorrow, to describe and describe the resistance and mimicry, first examined the orientalist behavior contained in the novel No Tomorrow. The results of this study showed: (1) the behavior of orientalism contained in the novel Tak Ada Esok is a domination carried out by the Dutch in order to exploit the Indonesian state, and orientalism behavior is also carried out by Johan along with guerrillas. (2) The resistance that occurs in the novel Tak Ada Esok is the fight of johan and hassan with Sudiarto with gerilyaw troops ... This study is a postcolonial study describing the resistance that occurred in the novel No Tomorrow by Mochtar Lubis. In this study using descriptive and deconstructive analysis methods. In order to be easy in conducting postcolonial study research, an intrinsic elemental approach is also used. The focus on this study is related to radical and passive resistance and mimicry that occurs in the novel No Tomorrow, to describe and describe the resistance and mimicry, first examined the orientalist behavior contained in the novel No Tomorrow. The results of this study showed: (1) the behavior of orientalism contained in the novel Tak Ada Esok is a domination carried out by the Dutch in order to exploit the Indonesian state, and orientalism behavior is also carried out by Johan along with guerrillas. (2) The resistance that occurs in the novel Tak Ada Esok is the fight of johan and hassan with Sudiarto with gerilyaw troops who performed mimicry to undermine the power of Japan and the Netherlands, it was in the postlonial study called radical resistance and mimicry conducted by the figures Johan and Hassan together sudiarto, is a mimicry to survive in order to undermine dutch power, with guerrilla forces, Johan did resistance directly or physical contact, it was in the postlonial study called radical resistance. who performed mimicry to undermine the power of Japan and the Netherlands, it was in the postlonial study called radical resistance and mimicry conducted by the figures Johan and Hassan together sudiarto, is a mimicry to survive in order to undermine dutch power, with guerrilla forces, Johan did resistance directly or physical contact, it was in the postlonial study called radical resistance. Keywords: Orientalism, Postcolonial, Resistance AbstrakKajian ini adalah sebuah kajian poskolonial yang mendeskripsikan resistenis yang terjadi dalam novel Tak Ada Esok karya Mochtar Lubis. Dalam penelitian ini menggunakan metode analisis deskriptif dan dekonstruksi. Agar mudah dalam melakukan penelitian kajian poskolonial, digunakan juga pendekatan unsur intrinsik. Fokus pada penelitian ini terkait dengan perlawanan radikal maupun pasif dan mimikri yang terjadi pada novel Tak Ada Esok, untuk menggambarkan dan mendeskripsikan perlawanan dan mimikri tersebut, terlebih dahulu dikaji perilaku orientalis yang terdapat dalam novel Tak Ada Esok. Hasil penelitian ini menunjukan: (1) perilaku orientalisme yang terdapat di dalam novel Tak Ada Esok merupakan dominasi yang dilakukan oleh Belanda agar dapat mengeksploitasi negera Indonesia, serta perilaku orientalisme juga dilakukan oleh Johan bersama pasukan gerilyawan. (2) Resistensi yang terjadi dalam novel Tak Ada Esok adalah perlawan tokoh Johan dan Hassan bersama Sudiarto dengan pasukan gerilyawan yang melakukan mimikri untuk meruntuhkan kekuasaan Jepang dan Belanda, hal itu di dalam kajian poskolonial disebut resistensi radikal dan mimikri yang dilakukan oleh tokoh Johan dan Hassan bersama Sudiarto, merupakan mimikri untuk bertahan hidup agar dapat meruntuhkan kekuasaan Belanda, dengan pasukan gerilyawan, Johan melakukan perlawanan secara langsung atau kontak fisik, hal itu di dalam kajian poskolonial disebut resistensi radikal. Kata kunci: Orientalisme, Poskolonial, Resistensi.